A case study of landfill gas potential at Kikås landfill - Assessment of environmental impacts and alternatives for mitigation - Larsson, Jonas (My University, 2014)
This thesis evaluates three different theoretical models to estimate landfill gas potential. Specifically, a case study to assess the gas potential at Kikås landfill and alternative mitigation measures has been conducted. Recent years, the waste sector has been increasingly acknowledged as a major contributor to emissions of greenhouse gases. A large part of these emissions are emissions of landfill gas (LFG). LFG consists of approximately 50 % carbon dioxide and 50 % methane. Methane is a strong greenhouse gas, which makes mitigation measures viable. On the behalf of the municipality of Mölndal, a case study was conducted with the aim of evaluating gas potential, environmental impact and options for mitigation if needed. A major threshold for conducting estimations of LFG potential is the major uncertainties related to both model parameters and site specific waste data. These uncertainties were to some extent evaluated by using three different models for estimation of LFG potential: the U.S EPA’s waste model LandGEM, IPCC’s waste model and the Dutch Afvalzorg’s model. The case study indicated a likely remaining gas potential of 2 100 – 3 250 ton methane for year 2015–2035,which is significant with respect to global warming. Nonetheless, uncertainties in estimated gas emissions are large. Therefore an investigation of actual gas flows by conducting test pumping is recommended.
Keywords: Annan naturvetenskap; Other Natural Sciences